Sosialisasi dan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) melalui Online Single Submission (OSS) kepada Pelaku Usaha Mikro di Desa Sukahayu Kecamatan Rancakalong Kabupaten Sumedang - Marthalina Marthalina; Utami Khairina (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2022)
The COVID-19 pandemic has had an impact on the weakening of the economy of the Sukahayu Village community which is marked by an increase in unemployment. Many people are trying their luck by opening a new business which administratively does not yet have a business license. From a total of around 400 UMKM in Sukahayu Village, only 179 UMKM have registered business licenses because most business actors carry out trading activities on weekdays, have not been able to use internet technology, and have not received information and know the urgency of making business permits. As a form of effort to overcome the problem of orderly administration at the Sukahayu Village Office, the community service team has carried out socialization and direct services for making business registration numbers (NIB) through online single submission (OSS) at the Sukahayu Village Office and door to door to people's homes that have micro business. The purpose of this community service activity is to provide an understanding of the importance of digital NIB and OSS to obtain ease of business legality as well as other documents such as corporate or individual NPWP. Community service activities are carried out with the method of socialization and service to the community which are carried out for approximately one month and have special targets for people who do not have a business identification number (NIB) but already own or run a micro business. This community service activity has coordinated directly with the Sukahayu Village government. The results of this community service activity were the issuance of 32 business registration numbers (NIB), increased knowledge and information from several people about the importance of business registration numbers for micro-enterprises in Sukahayu Village and increased public desire to register their businesses legally which was marked by the entry of proposed documents. only 17 pieces. Suggestions for optimizing the making of NIB in Sukahayu Village is that it takes the commitment and consistency of the Sukahayu Village government to continue socialization activities, door to door services and more serious assistance for micro business actors because there are still more than 200 micro businesses that have not been registered through OSS and there are still many people who do not understand the importance of business registration numbers for business actors due to the assumption that people think that taking care of business permits and legalities takes a long time and is a complicated matter. This condition really needs to be considered and followed up by the Sukahayu Village government in collaboration with the relevant office.